Membentuk Karakter Anak Melalui Kearifan Lokal: Nyanyian Anak di Kecamatan Saronggi - Moh. Juhdi; Moh. Fauzi (JKI (Jurnal Konseling Indonesia), 2017)
Based on the development of literature in Indonesia, especially oral literature (folklore) has an important role. In addition, the oral literature (folklore) has its own uniqueness both in terms and functions contained in it so that from the uniqueness of the oral literature that exist in the regions has its own meaning for the community such as the nuances of children's singing in the village of Talang Kecamatan Saronggi. This phenomenon is one of the reasons for more in-depth review. The study of oral literature (singing children) to describe and provide an overview of the character formation of children in the singing of children in the village of Talang Kecamatan Saronggi. The method used in this research is descriptive qualitative method karenan data obtained descriptive data words and data orally, so here the researchers used a qualitative approach in reviewing something heard and seen from the results of field observation to be used as research data. Based on the hail data analysis of children's songs in the village of Talang Kecamatan Saronggi have and functions that can shape the child's character like anything, hard work, friendship, social care, love for peace and have a sense of responsibility.